a) -4,8x8,9 + 8,9 x (-5,2) = 8,9 (-4,8-5,2) = 8,9 (-48/10-52/10) = 89/10 x (-100/10) = -89
b) -1,2 x (-7 si 9/13) - (-1,2) x 2 si 4/13 = -1,2 (-7 si 9/13 - 2 si 4/13) = -1,2 (-100/13 - 30/13) = -12/10 x (-130/13) = -12/10 x (-10) = 12
c) -2 si 3/7 x 2 si 4/5 + (-2 si 3/7) x 4 si 1/5 = -2 si 3/7 (2 si 4/5 + 4 si 1/5) = -17/7 x (14/5+21/5) = -17/7 x 35/5 = -17/7 x 7 = -17
d) -32,2 x 7 si 10/13 + 2 si 3/13 x (-32,2) = -32,2 (7 si 10/13 + 2 si 3/13) = -322/10 (101/13 + 29/13) = -322/10 x 130/13 = -322/10 x 10 = -322